Excavating Repositories: Academic Research Projects Using Archaeological Collections. Issue 3 (August 2019) - Schiappacasse, Paola A.
ABSTRACT: Around the world, archaeological collections are curated in museums, universities, foundations, government agencies, and other organizations. Some are carefully documented and readily accessible, while others are languishing in substandard conditions as a direct result of the curation crisis. This article highlights the value of collection-based research. It encourages the mutually beneficial approach of training students in both collection preservation and collection-based research and demonstrates other ways to obtain data for research projects, aside from excavation. Using my collections-based research carried out in Puerto Rico and the continental United States as a case study, I draw attention to the valuable information that can be derived from acquisition and accession documents and offer ways to incorporate new datasets. This allows for more accurate narratives of collections' historiographies. Abstract : En todo el mundo, las colecciones arqueológicas se curan en museos, universidades, fundaciones, agencias gubernamentales y otras organizaciones. Algunas están cuidadosamente documentadas y son fácilmente accesibles, mientras que otras languidecen en condiciones por debajo de los estándares establecidos como resultado directo de la crisis de curación. Este artículo destaca el valor de la investigación basada en colecciones. También fomenta el enfoque de beneficio mutuo de capacitar estudiantes en la conservación de colecciones y en los estudios que se pueden hacer con estas, y demuestra otras formas de obtener datos para proyectos de investigación, además de las excavaciones. Utilizando mis trabajos con colecciones, en Puerto Rico y los Estados Unidos continentales, como casos de estudio, traigo a la atención la información valiosa que se puede obtener de los documentos de adquisición y registro, y ofrezco formas de incorporar nuevos conjuntos de datos. Esto permite narrativas más precisas de las historiografías de las colecciones.